2015
DOI: 10.1162/jocn_a_00741
|View full text |Cite
|
Sign up to set email alerts
|

Regional White Matter Variation Associated with Domain-specific Metacognitive Accuracy

Abstract: Abstract■ The neural mechanisms that mediate metacognitive ability (the capacity to accurately reflect on oneʼs own cognition and experience) remain poorly understood. An important question is whether metacognitive capacity is a domain-general skill supported by a core neuroanatomical substrate or whether regionally specific neural structures underlie accurate reflection in different cognitive domains. Providing preliminary support for the latter possibility, recent findings have shown that individual differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
56
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 96 publications
(132 reference statements)
11
56
0
Order By: Relevance
“…This is consistent with previous studies that found correlations in mean confidence levels across different tasks, both within and between sensory modalities (Ais et al, 2016, Song et al, 2011) and between perceptual and memory domains (Baird et al, 2015, Baird et al, 2013, McCurdy et al, 2013). Some studies also found a task-dependent component of metacognitive bias which was attributed to differences in difficulty between tasks (Baird et al, 2015, Baird et al, 2013, Song et al, 2011). We did not find a task-dependent component of metacognitive bias, even though the innocuous warmth discrimination task was more difficult than the nociceptive pain discrimination task and the visual contrast discrimination task.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous studies that found correlations in mean confidence levels across different tasks, both within and between sensory modalities (Ais et al, 2016, Song et al, 2011) and between perceptual and memory domains (Baird et al, 2015, Baird et al, 2013, McCurdy et al, 2013). Some studies also found a task-dependent component of metacognitive bias which was attributed to differences in difficulty between tasks (Baird et al, 2015, Baird et al, 2013, Song et al, 2011). We did not find a task-dependent component of metacognitive bias, even though the innocuous warmth discrimination task was more difficult than the nociceptive pain discrimination task and the visual contrast discrimination task.…”
Section: Discussionsupporting
confidence: 93%
“…This finding accords well with the known lateralization of the attention system (48). Such a lateralization is also reported in the metacognition literature, where interindividual differences in metacognitive abilities correlate with differences in white matter structure (49), fMRI signals (50), and even lesions (51) that are mostly observed in the right hemisphere, although not always (52).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, the brain basis of MC is still unknown. On the one hand, functional and structural neuroimaging studies have frequently localized substrates of MC in prefrontal regions [Baird et al, ; Fleming et al, ; McCaig et al, ; Yokoyama et al, ], possibly suggesting some domain‐generality. In an influential theory, MC was related to mentalizing, also called Theory of Mind (ToM) [Frith, ], where taking the perspective on one's own actions may rely on processes and (largely prefrontal) networks similar to those involved in taking the perspective of others [Lombardo et al, ; Frith, ].…”
Section: Introductionmentioning
confidence: 99%